2007
DOI: 10.1093/toxsci/kfl180
|View full text |Cite
|
Sign up to set email alerts
|

Troglitazone-Induced Hepatic Necrosis in an Animal Model of Silent Genetic Mitochondrial Abnormalities

Abstract: Troglitazone, a first-generation thiazolidinedione antidiabetic drug, was withdrawn from the market due to an unacceptable risk of idiosyncratic hepatotoxicity. Troglitazone does not cause hepatotoxicity in normal healthy rodents, but it produces mitochondrial injury in vitro at high concentrations. The aim of this study was to explore whether genetic mitochondrial abnormalities might sensitize mice to hepatic adverse effects of troglitazone. We used heterozygous superoxide dismutase 2 (Sod2(+/-)) mice as a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(121 citation statements)
references
References 41 publications
2
115
4
Order By: Relevance
“…These mitochondrial changes were inhibited by N-acetyl cysteine [15]. Furthermore, enhanced susceptibility to cell injury in conditions of preexisting oxidative stress/mitochondrial impairment has been demonstrated by Ong and Boelsterli in a mouse model of silent mitochondrial abnormality [44]. This is relevant to patients with pre-existing oxidative stress due to NAFLD or glutathione depletion.…”
Section: Reactive Metabolite/reactive Oxygen Species (Ros)mentioning
confidence: 77%
See 1 more Smart Citation
“…These mitochondrial changes were inhibited by N-acetyl cysteine [15]. Furthermore, enhanced susceptibility to cell injury in conditions of preexisting oxidative stress/mitochondrial impairment has been demonstrated by Ong and Boelsterli in a mouse model of silent mitochondrial abnormality [44]. This is relevant to patients with pre-existing oxidative stress due to NAFLD or glutathione depletion.…”
Section: Reactive Metabolite/reactive Oxygen Species (Ros)mentioning
confidence: 77%
“…Many techniques are currently available [9,10]. The use of better animal models that replicate the human disease phenotype [44,64] could also unmask latent toxic potentials.…”
Section: Discussionmentioning
confidence: 99%
“…The role of SOD2 in drug-induced hepatotoxicity has proven contradictory. Ong and coworkers 19 reported that Sod2 þ/À knockout mice developed increased serum alanine aminotransferase activity and hepatic necrosis after prolonged troglitazone administration. However, Fujimoto and coworkers 20 were unable to reproduce these results.…”
Section: Discussionmentioning
confidence: 99%
“…Following exposure, the toxic moiety induces some type of stress or functional disturbance, with mitochondrial injury being one of the most important targets recognized. 21,22 A number of adaptation mechanisms are then initiated to counteract the inflicted damage. 23,24 In addition, innate and adaptive immune responses are other factors of interest which determine the progression and severity of liver injury.…”
Section: Mechanisms Of Haart-related Hepatotoxicitymentioning
confidence: 99%